An Update on Anti-Helicobacter Pylori Treatment in Children - Renuka Khurana; Lori Fischbach; Naoki Chiba; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
Previous consensus statements have recommended one- to two-week proton pump inhibitor (PPI)-based triple therapies with clarithromycin and either amoxicillin or metronidazole as first-line treatments for children with Helicobacter pylori infection. The objective of the present review was to summarize data from pediatric studies that have examined treatment efficacy, safety, drug resistance and reinfection rates related to anti-H pylori therapies. Data from a recent meta-analysis of pediatric studies were used along with the authors' existing databases and searches of individual studies. Regimens that were identified as greater than 80% efficacious in children included a two-week therapy with a nitroimidazole and amoxicillin in Europe; a two-week regimen of bismuth, amoxicillin and metronidazole in developed countries (except Spain); a one- to two-week regimen of a PPI, clarithromycin and amoxicillin in Northern Europe, Asia and the Middle East; and a two-week regimen of a PPI, clarithromycin and metronidazole in Canada. Although recommended as a first-line treatment in adults, two-week treatment with a PPI, clarithromycin and amoxicillin eradicated only 68% of H pylori infections in North American children. Treatment efficacy was reduced in the presence of metronidazole and/or clarithromycin resistance. Further studies of anti-H pylori treatments in children in North America and developing countries are warranted.